Pteryxin attenuates LPS-induced inflammatory responses and inhibits NLRP3 inflammasome activation in RAW264.7 cells. (10th February 2022) - Zhen, Dong; Xuan, Tian-qi; Hu, Boqin; Bai, Xue; Fu, Dan-ni; Wang, Yu; Wu, Yun; Yang, Jingfeng; Ma, Qianqian
Abstract: Ethnopharmacological relevance: Pteryxin is a natural coumarin compound that is found in "Qianhu", a traditional Chinese medicine, which possesses heat-clearing and detoxifying functions according to the theory of Traditional Chinese Medicine. Despite its medicinal effects, its anti-inflammatory and mechanisms of actions have not been established. Aim of this study: This study aims to evaluate the anti-inflammatory property and reveal the possible anti-inflammatory mechanisms of pteryxin. Material and methods: LPS-induced RAW 264.7 macrophages and LPS-induced zebrafish model were used for the anti-inflammatory activity determination of pteryxin. The level of NO, PEG2, TNF-α and IL-6 were measured by ELISA. The accumulation of NO and ROS was stained and observed by a fluorescence microscopy. The nuclear translocation of NF-κB p65 and formation of NLRP3 inflammasome complex in LPS-induced RAW 264.7 macrophage cells were analyzed by immunofluorescence assay. The expression level of iNOS, IL-6, COX-2, TNF-α, p-p38, p38, ERK, JNK, p-ERK, p-JNK, IKK, IκB-α, p-IKK, p-IκB-α, p65, NLRP3, p-p65, Caspase 1 (p 20), ASC, and GAPDH were determined by Western blotting. Results: Lipopolysaccharide (LPS)-induced prostaglandin E2 (PGE2) and nitric oxide (NO) secretions were found to be downregulated by pteryxin. Moreover, pteryxin significantly suppressed inflammatory factor secretion in LPS-treated RAW 264.7 cells. Mechanistically, pteryxin significantly downregulated NF-κB/MAPK activation. Moreover, pteryxin inhibited caspase-1 and NLRP3 activation and formation of ASC specks in RAW 264.7 cells, implying that pteryxin inhibits inflammasome assembly, which is a signal for NLRP3 inflammasome activation. In conclusion, pteryxin blocks NF-κB/MAPK signaling, and suppresses the initiation and activation of NLRP3 thereby preventing inflammation. Conclusion: Pteryxin is a potential treatment option for inflammatory-related diseases. Graphical abstract: Image 1 Highlights: Pteryxin inhibits LPS-induced inflammatory responses. Anti-inflammatory effects of pteryxin are associated with inhibited NF-κB and MAPK signaling pathway. Pteryxin could suppresses the priming and activating steps of NLRP3 inflammasomes.